SERUM INTERLEUKIN-33 LEVELS ARE ELEVATED BUT NOT ASSOCIATED WITH DISEASE ACTIVITY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Ulusoy, Hasan; Akgol, Gurkan; Gulkesen, Arif; Kaya, Arzu; Kaman, Dilara (Carbone Editore, 2020)
Introduction. Interleukin (IL)-33 is a new member of the IL-1 superfamily. After cellular damage, IL-33 is released into the extracellular space and functions as an alarmin to induce the innate immunity. Recent studies suggest that IL-33 can also induce T helper-1 (Th1), Th2 and Th17 mediated adaptive immune responses. So, as a pro-inflammatory cytokine, IL-33 plays an important role in the pathogenesis of autoimmune and inflammatory diseases. In this recpect, we also assessed the effect of serum IL-33 level in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) which are the most common inflammatory arthritis. Materials and methods: Thirty RA patients, 30 AS patients, and 30 healthy controls were recruited. Blood samples were obtained for detecting serum IL-33 levels. The disease activity was assessed with diseases activity score-28 in RA patients and with the Bath ankylosing spondylitis disease activity index in AS patients. All patients were evaluated for severity of pain, fatigue, the physicians's global assessment and the patient's global assessment. Morning stiffness was evaluated in minutes. Functional status of the all patients were evaluated with the health assesment questionnaire. Patients with AS were also assessed with the Bath ankylosing spondylitis functional index. Relationship between serum IL-33 levels and disease activity parameters were assessed. Results: Serum IL-33 levels were higher in RA patients than in AS patients and healthy controls. Increased serum levels of IL-33 were not correlated with the disease activity parameters in RA patients. There was no significant relationship between serum IL-33 levels and rheumatoid factor or anti-cyclic chrullinated peptide antibody levels in RA patients. Serum IL-33 levels were not significantly different in patients with AS and healthy conrols. Conclusion: Serum IL-33 levels were higher in patients with RA than in patients with AS and healthy controls. But serum IL-33 level was not associated with the disease activity, this result may be due to the cross-sectional design of the study. A better understanding the pathogenesis of diseases is important to develop new therapeutic agents. Our study suggest that IL-33 may have a complex role in the pathogenesis of RA and may be a promising target for the treatment of RA. But larger follow-up studies are needed to support this opinion.
Keywords: Ankylosing spondylitis; Disease activity; Interleukin; IL-33; Rheumatoid arthritis